The impact of employee perceptions of training on organizational commitment and turnover intentions: a study of multinationals in the Chinese service sector - Newman, A.; Thanacoody, R.; Hui, Wendy (Routledge, 2011)
This study examines the impact of employee perceptions of training on organizationalcommitment, and the latter’s relationship with turnover intentions. Structured equationmodelling is conducted on survey data from 437 Chinese employees of fivemultinational enterprises operating in the Chinese service sector. The results of thesurvey are consistent with social exchange theory. They highlight the importance oftraining as a tool to enhance the affective organizational commitment of employees,and reduce turnover. The findings differ from that of previous studies in non-Chinesesettings. No evidence was found to indicate that motivation to learn and the perceivedbenefits of training impact on the organizational commitment of employees. This maybe explained by three factors: the involuntary nature of employee training, the limitedcareer development opportunities on offer to local employees of multinationalenterprises and the difficulty employees face in applying learnt skills given culturaldifferences. The implications for research and practice are discussed.